Nursing management towards quality care - Venzon, Lydia M.; Nagtalon, Jennifer M.V. (Quezon City, Philippines : C & E Publishing Inc., 2006)
This book is designed for practicing nurse-managers and for those who are preparing themselves for positions of responsibility.
The nursing management process: an overview -- Planning for the nursing service -- Organizing the nursing service -- Directing the nursing services -- Controlling -- An overview of the nursing process -- Assessing the patient's health care, nursing needs, and problems -- Nursing diagnosis -- Developing the nursing care plan -- Implementing the nursing care plan -- Evaluating the quality of nursing care -- Ethnico-legal aspects in nursing practice.
Includes index.
Keywords: NURSING, SUPERVISORY -- PHILIPPINES